Anticipatory Waivers of Consent for Pediatric Biobanking. Issue 2 (20th March 2019) - Hartsock, Jane A.; Schwartz, Peter H.; Waltz, Amy C.; Ott, Mary A.
ABSTRACT: As pediatric biobank research grows, additional guidance will be needed about whether researchers should always obtain consent from participants when they reach the legal age of majority. Biobanks struggle with a range of practical and ethical issues related to this question. We propose a framework for the use of anticipatory waivers of consent that is empirically rooted in research that shows that children and adolescents are often developmentally capable of meaningful deliberation about the risks and benefits of participation in research. Accordingly, bright‐line legal concepts of majority or competency do not accurately capture the emerging capacity for autonomous decision‐making of many pediatric research participants and unnecessarily complicate the issues about contacting participants at the age of majority to obtain consent for the continued or first use of their biospecimens that were obtained during childhood. We believe the proposed framework provides an ethically sound balance between the concern for potential exploitation of vulnerable populations, the impetus for the federal regulations governing research with children, and the need to conduct valuable research in the age of genomic medicine.